2020
DOI: 10.1108/mrr-06-2019-0254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of investor sentiment and its antecedent on investment decision-making using partial least square technique

Abstract: Purpose The purpose of this paper is to determine whether individual investor sentiment and its factors influence investment decision-making behavior in the Indian stock market. The study contributes to the novel conceptual framework that integrates the impact of investor sentiment and outlines the role of its factors (herding, media factor, advocate recommendation and social interaction) during the investment decision-making process. Design/methodology/approach In this paper, data were collected using a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 105 publications
0
8
1
Order By: Relevance
“…Among all these factors, social interaction has the lowest effect on investor sentiment. The study also revealed that investor sentiment positively impacts investment decision-making [9].…”
Section: Literature Reviewmentioning
confidence: 78%
See 2 more Smart Citations
“…Among all these factors, social interaction has the lowest effect on investor sentiment. The study also revealed that investor sentiment positively impacts investment decision-making [9].…”
Section: Literature Reviewmentioning
confidence: 78%
“…Awareness can be defined as a financial awareness as "the ability to make sound judgments and to make effective decisions regarding the use and management of money" [9]. Awareness exists to share information or ideas through the internet, media, social interactions, recommendations from friends, relatives, or intermediaries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[41][44]. Fifth, future research can be considered the effects of demographic characteristics such as age, level of education, experience, gender in investors in determining investment decisions [45].…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…When investors make decisions, their emotions influence their decision (Ángeles L opez-Cabarcos et al, 2020). Henry (2008) examining the role of emotions in investors' decision-making process, they found that tone of communication affects investors 'decisions .In research of Haritha and Uchil (2020), the effect of investor sentiment on their decisions was examined. Their research results showed that herding, media factor, advocate recommendation and social interaction significantly and positively influence the investor sentiment.…”
Section: Investor Sentimentmentioning
confidence: 99%